Breast Implant Surgery in Bangladesh: An Experience of 126 cases (Bangladesh Journal of Plastic Surgery, 2011)
Augmentation mammoplasty is one of the common plastic surgical operations in the western countries. The procedure  has received particular attention among patients with hypo-plastic breasts. The first silicone breast implant was  performed in 1963 by Cronin and Gerow, and at present more than 250,000 breast implants are done every year in the USA alone. Due to skepticism and ignorance this surgery took a very long time to become popular in Bangladesh. We started breast implant surgery in Bangladesh in September 2001. Since then it gradually became popular and is now a rather common procedure in our centre. In spite of our conservative culture and religious taboos, women in  Bangladesh are no longer lagging behind in deriving the benefit of this wonderful procedure.  The study was done at a private hospital from September 2001 to September 2008. A total of 126 cases were done, 125 being females and 1 male. Complications were minimal and the overall results very encouraging. The result of  the present work evidenced that silicone breast implants can boost confidence by alleviating depression in women  of different age groups with hypoplastic breasts. Research studies have further revealed that silicone implant does not impair lactation. Key words: Silicone implant; augmentation mammoplasty DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8799 BDJPS 2010; 1(2): 10-13